(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2020)
We have studied the electromagnetically induced transparency for a two level ensemble interacting with two orthogonal optical modes. We have made a approach for a multimode silicon waveguide coupled to a plasmonic resonator array. We have shown that a simple periodic ensemble of resonant metal nanoparticles within a dielectric waveguide supported a transparent waveguide plasmon polariton mode for guided slow light propagation. Such systems inhert the strongly dispersive properties of the nanoparticles embedded in the waveguide but do not succumb to the associated absorptive losses by utilizing the system’s transparency Light propagation through the system provided extremely strong dispersion from the resonators, but suffers very low propagation loss by exploiting the system’s transparency. Dispersion is controllable by tuning the coupling strength of localized plasmon and waveguide modes. We have found that atomic electromagnetically induced transparency occurred for a non zero pump field allowing mutual coupling of all states and induced destructive quantum interference of the probe field’s absorption via the transition. The obtained results were found in good agreement with previously obtained results.